2021
DOI: 10.1038/s41467-021-21031-8
|View full text |Cite
|
Sign up to set email alerts
|

Conserved strategies of RNA polymerase I hibernation and activation

Abstract: RNA polymerase (Pol) I transcribes the ribosomal RNA precursor in all eukaryotes. The mechanisms ‘activation by cleft contraction’ and ‘hibernation by dimerization’ are unique to the regulation of this enzyme, but structure-function analysis is limited to baker’s yeast. To understand whether regulation by such strategies is specific to this model organism or conserved among species, we solve three cryo-EM structures of Pol I from Schizosaccharomyces pombe in different functional states. Comparative analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“… a , Domain composition of the human RPA43 (top) and its yeast A43 homologs: S. cerevisiae (middle; PDB 5M64 ) 25 and S. pombe (bottom; PDB 7AOE ) 43 . The colored bar indicates the region modeled in the structures denoted as ‘built’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a , Domain composition of the human RPA43 (top) and its yeast A43 homologs: S. cerevisiae (middle; PDB 5M64 ) 25 and S. pombe (bottom; PDB 7AOE ) 43 . The colored bar indicates the region modeled in the structures denoted as ‘built’.…”
Section: Resultsmentioning
confidence: 99%
“…3a ). Consequently, previous studies using S. cerevisiae 14 , 15 or S. pombe 43 have focused on outliers within the tree of life. We next investigated the phylogenomic conservation of the yeast extensions of subunits A135 (residues 1135–1168) and ABC23 (residues 50–68), which contact the stalk (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although both polymerase dimers are related by a two-fold axis (C2 axis), the C2 axis of the two dimers are rotated by ∼45 degrees with respect to each other (Figure 4C ). The exact location of the C2 axis can vary because the Pol I dimers show some flexibility with respect to their relative orientation ( 6 , 8 ). In our dataset, we could also classify two more distinct states of the Pol II dimer that display a rotation of one Pol II copy with respect to another, leading to slightly different locations of the C2 axis ( Supplementary Figure S6 and Supplementary Movie S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pol I dimerization was initially observed by electron microscopy at low resolution ( 3 ) and later in high-resolution crystal structures ( 4 , 5 ). More recently, a higher resolution structure of the Schizosaccharomyces pombe Pol I dimer was determined by cryo-EM ( 6 ). Structural studies indicated that the Pol I dimer represents a repressed state of the enzyme, leading to a model for Pol I regulation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, based on our structures and phylogenetic analysis, we show that Pol I in general contains 13 subunits, except in the few species of fungi. Consequently, previous studies using S. cerevisiae 19,20 or S. pombe 42 have focused on outliers within the tree of life. We then investigated the phylogenomic conservation of the yeast extensions of subunits A135 (1135-1168) and ABC23 (50-68) which contact the stalk (Fig.…”
Section: Human Pol I Stalk Contains a Single Subunitmentioning
confidence: 99%